Proceedings of the 3rd Progress in Social Science, Humanities and Education Research Symposium (PSSHERS 2021) 2022
DOI: 10.2991/978-2-494069-33-6_24
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Motor Skills Level of TK Students During the Covid 19 Pandemic

Abstract: Possessing motor abilities at a young age has a long-term impact on physical activity. Kindergarten children engaged in online learning, increased screen usage, and spent time at home during the COVID-19 epidemic. There is a lot of research that evaluates the influence of the COVID-19 pandemic on all parts of human existence, but little work that ties it to kindergarten pupils' mobility skills during the epidemic. The scarcity of literature on the development of movement abilities in kindergarten pupils during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Our study contributes to the growing body of evidence by demonstrating a temporal association between the COVID-19 pandemic and an increased incidence of anisometropia in children. Another possible explanation is that the pandemic may have reduced the outdoor exposure and physical activity of children (16,17), which may have affected their ocular development and refractive error. Several studies have reported that outdoor exposure and physical activity may have protective effects against myopia and anisometropia by stimulating dopamine release, reducing choroidal thickness and enhancing retinal image quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study contributes to the growing body of evidence by demonstrating a temporal association between the COVID-19 pandemic and an increased incidence of anisometropia in children. Another possible explanation is that the pandemic may have reduced the outdoor exposure and physical activity of children (16,17), which may have affected their ocular development and refractive error. Several studies have reported that outdoor exposure and physical activity may have protective effects against myopia and anisometropia by stimulating dopamine release, reducing choroidal thickness and enhancing retinal image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Due to lockdown measures and school closures, many children spent more time indoors and engaged in near work activities such as online learning, reading and gaming (15). Recent studies have highlighted the potential impact of the COVID-19 pandemic on various aspects of healthcare (16,17), including eye care (18)(19)(20). Disruptions in access to healthcare services, changes in lifestyle and screen time patterns, and increased psychological stress during the pandemic may have influenced the development of ocular conditions, including anisometropia, among children.…”
Section: Introductionmentioning
confidence: 99%
“…From a procedural standpoint, circuit training is a physical training method in which an athlete moves sequentially from one designated training station to another in the most efficient manner. In circuit training program planning, exercises are selected according to individual needs (J Bovas & C. S Pradeep, 2020;Jadhav, 2020;Pranoto et al, 2023). In general, sports science students should initially undergo general conditioning before gradually progressing to specific training for the sports skills they are interested in.…”
Section: Introductionmentioning
confidence: 99%
“…Perkembangan keterampilan gerak dasar di masa sekolah ialah sebuah prosedur dasar yang mendorong keterlibatan dalam aktivitas fisik anak (Pranoto et al, 2023). Pemahaman dasar bahwa gerak diorganisasikan sebagai suatu aktivitas, tidak hanya untuk memahami perkembangan motorik tetapi juga untuk memahami aspek perkembangan lainnya (Von Hofsten, 2004).…”
unclassified